Analysis of Polyphenol Extract from Hazel Leaf and Ameliorative Efficacy and Mechanism against Hyperuricemia Zebrafish Model via Network Pharmacology and Molecular Docking - Xinhe Wang; Jiarui Zhao; Zhi Lin; Jun Li; Xiaowen Li; Xinyi Xu; Yuchen Wang; Guangfu Lv; He Lin; Zhe Lin (Molecules, 2024)
Hazel leaf, a by-product of hazelnuts, is commonly used in traditional folk medicine in Portugal, Sweden, Iran and other regions for properties such as vascular protection, anti-bleeding, anti-edema, anti-infection, and pain relief. Based on our previous studies, the polyphenol extract from hazel leaf was identified and quantified via HPLC fingerprint. The contents of nine compounds including kaempferol, chlorogenic acid, myricetin, caffeic acid, p-coumaric acid, resveratrol, luteolin, gallic acid and ellagic acid in hazel leaf polyphenol extract (ZP) were preliminary calculated, among which kaempferol was the highest with 221.99 mg/g, followed by chlorogenic acid with 8.23 mg/g. The inhibition of ZP on α-glucosidase and xanthine oxidase activities was determined via the chemical method, and the inhibition on xanthine oxidase was better. Then, the effect of ZP on hyperuricemia zebrafish was investigated. It was found that ZP obviously reduced the levels of uric acid, xanthine oxidase, urea nitrogen and creatinine, and up-regulated the expression ofOAT1 and HPRT genes in hyperuricemia zebrafish. Finally, the targeted network pharmacological analysis and molecular docking of nine polyphenol compounds were performed to search for relevant mechanisms for alleviating hyperuricemia. These results will provide a valuable basis for the development and application of hazel leaf polyphenols as functional ingredients.